The Effects of Interstate Banking on Commercial Banks' Risk and Profitability - Chong, Beng Soon (The Review of Economics and Statistics, 1991)
Historically, the effect of interstate banking on the risk and profitability of commercial banks has been a controversial issue. Using capital market data and an event study methodology, the author tests the effects of interstate banking. The findings of this paper reject the hypothesis that interstate banking has no effect on banks' risk and profitability. The evidence supports the argument that interstate banking benefits commercial banks in terms of increased profitability, but the increase in profitability is also associated with significant increases in the banks' exposure to market risk. Copyright 1991 by MIT Press.